The Role of the Teacher in the Character Education Strengthening Program for Grade V Elementary School Students - Citra Veronika; Febrina Dafit (Jurnal Ilmiah Sekolah Dasar, 2022)
Education is a process of educating and requires students to achieve certain goals in the form of positive changes from within students. The desired change is part of a process towards maturity that occurs continuously in students' lives. This research is motivated by the low character of the younger generation, especially at the elementary school level. Therefore, the government implements a character education strengthening program at every level of education. This study analyzes the teacher's role in implementing character education strengthening programs for fifth-grade elementary school students. This research is research with a qualitative approach. Data were collected using interview and observation methods. The results show that many character education strengthening programs have been implemented in elementary schools and are following the five character values ​​of students, one of which is religious values ​​by getting used to praying before the start of learning. One of the teacher's roles in strengthening character education programs is to develop learning implementation plans and carry out learning and assessments that integrate the main values ​​of strengthening character education.